Dynamic testing and analysis of turbine generator shafting. Issue 23 (16th December 2019) - Tang, Changliang; Wang, Liyong; Chen, Tao
Abstract : With the world's energy shortage, the scholars all over the world have done a lot of research work on the efficient use of energy, energy‐saving emission reduction, and the development of new energy. Turbine generators have a wide range of applications in energy recovery. In this study, a new type of turbine generator structure is proposed. Four disc‐type permanent magnet motors are symmetrically mounted on the shafting, and are supported by gas hydrostatic bearing. The vibration tests of the shafting were carried out. The vibration characteristics of the shafting were analysed by using the bode diagram, the time‐waterfall map, the bifurcation diagram, the shaft orbits at the typical speeds, and the Poincare maps, which can provide references for developing high‐speed turbine generators.